Selection and Analysis of Interface User Structure of the Local Positioning System - D. V. Bogdanov; D. V. Gayvoronsky (Известия высших учебных заведений России: Радиоэлектроника)
Building of user interface of the local positioning system is considered. It is shown that to achieve centimeter positioning accuracy the application of ultra-wideband signal technology with separate transmission of data message is required.